‘WNT-er is coming’: WNT signalling in chronic lung diseases - Baarsma, H A (Thorax, 2017)
Chronic lung diseases represent a major public health problem with only limited therapeutic options. An important unmet need is to identify compounds and drugs that target key molecular pathways involved in the pathogenesis of chronic lung diseases. Over the last decade, there has been extensive interest in investigating Wingless/integrase-1 (WNT) signalling pathways; and WNT signal alterations have been linked to pulmonary disease pathogenesis and progression. Here, we comprehensively review the cumulative evidence for WNT pathway alterations in chronic lung pathologies, including idiopathic pulmonary fibrosis, pulmonary arterial hypertension, asthma and COPD. While many studies have focused on the canonical WNT/β-catenin signalling pathway, recent reports highlight that non-canonical WNT signalling may also significantly contribute to chronic lung pathologies; these studies will be particularly featured in this review. We further discuss recent advances uncovering the role of WNT signalling early in life, the potential of pharmaceutically modulating WNT signalling pathways and highlight (pre)clinical studies describing promising new therapies for chronic lung diseases.